SEJARAH PERKEMBANGAN PENGATURAN TINDAK PIDANA KORUPSI DI INDONESIA - Franky Damanik; Finish Masa Derita Gea; Rosmalinda Rosmalinda (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Corruption is a problem that until now cannot be resolved and has caused quite large losses to the state. Reality shows that the value of state losses is much greater than the money that has been returned to the state. Corruption can paralyze national development. In society, this corrupt practice can be found in various modus operandi and can be carried out by anyone, from various social and economic strata. Talking about corruption cannot be separated from the long history of the legal system for criminal acts of corruption in Indonesia. The focus of this article will look at developments in handling corruption based on data released by relevant bodies and looking at the history of legal system policies related to the rules of criminal acts of corruption in Indonesia through comparisons from several eras. This writing tries to reveal interesting things related to the history of corruption criminal policies in Indonesia.